Perspektif Teologi Inkulturasi terhadap Tradisi Lom Plai pada Komunitas Katolik Dayak Wehea - Patrisia Rera Bato; Intansakti Pius X; Emmeria Tarihoran (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the Lom Plai tradition of the Dayak Wehea community from the perspective of Catholic inculturation theology. Although this tradition has been widely studied from an anthropological perspective, no research has specifically examined the meaning of its values, symbols, and rituals in the light of inculturation. Therefore, this study is important to see the possibility of dialogue between the Gospel and local culture. The purpose of this study is to understand how elements of Lom Plai culture can be interpreted and processed within the framework of inculturation theology and how the values ​​contained therein can enrich the pastoral life of the community. The study uses a literature review method with a qualitative-contextual theological approach through analysis of theological literature, Church documents, and ethnographic studies of the Dayak Wehea. The research findings indicate that the values ​​of harvest gratitude, respect for the land, community solidarity, and symbols such as rice and thanksgiving rituals are aligned with Christian spirituality and have the potential to be integrated into pastoral practice. The implications of this study emphasize the need for ongoing discernment so that the inculturation process runs authentically, enriches the community's faith, and maintains the cultural identity of the Wehea community.